2016
DOI: 10.1038/nm.4201
|View full text |Cite|
|
Sign up to set email alerts
|

Human antibody repertoire after VSV-Ebola vaccination identifies novel targets and virus-neutralizing IgM antibodies

Abstract: Development of an effective vaccine against Ebola virus is of high priority. However, knowledge about potential correlates of protection and the durability of immune response after vaccination is limited. Here, we elucidate the human antibody repertoire after administration of vesicular stomatitis virus (VSV)-Ebola vaccine at 3 million, 20 million and 100 million plaque-forming units (PFU) and homologous VSV-Ebola vaccine boost in healthy adult volunteers. Whole genome-fragment phage display libraries, express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
94
1
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(105 citation statements)
references
References 39 publications
9
94
1
1
Order By: Relevance
“…Antibodies that recognize the IEF-linked, more accessible Tier 1 epitopes may even take precedence in polyclonal responses elicited by vaccination. Indeed, GP1/Head and glycan cap mAbs were the most abundantly recognized epitopes by antibodies in vaccinee sera (Khurana et al, 2016) after the first dose of rVSV-based EBOV vaccine (Regules et al, 2015). The frequency of these antibodies persisted after the second vaccine dose, whereas that of HR2 and membrane-proximal antibodies decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies that recognize the IEF-linked, more accessible Tier 1 epitopes may even take precedence in polyclonal responses elicited by vaccination. Indeed, GP1/Head and glycan cap mAbs were the most abundantly recognized epitopes by antibodies in vaccinee sera (Khurana et al, 2016) after the first dose of rVSV-based EBOV vaccine (Regules et al, 2015). The frequency of these antibodies persisted after the second vaccine dose, whereas that of HR2 and membrane-proximal antibodies decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Samples of freshly prepared antibody (200 l) at 5-fold dilutions (starting concentrations of 50 g/ml for MAbs 1E8, 5H11, and 7F12 and of 10 g/ml for other MAbs) were injected at a flow rate of 50 l/min (120-s contact time) for association, and dissociation was performed over a 600-s interval (at a flow rate of 50 l/min). Responses from the protein surface were corrected for the response from a mock surface and for measurements from a separate, buffer-only injection as described before (27,28). Binding kinetics for the antibody-antigen interaction was calculated by a bivalent analyte model using Bio-Rad ProteOn manager software (version 3.0.1).…”
Section: Methodsmentioning
confidence: 99%
“…2 and 3C), they likely bind to different antigenic domains. In addition, they have different binding affinities to NA, as indicated by the equilibrium dissociation constants (K D s) ( Table 1) measured with surface plasmon resonance (SPR) (27,28). 10F4 and 2F6 have higher avidity for NA (K D values of 1.4 and 3.7 nM, respectively) than 1E8 and 11B2 (no binding was detected by SPR at the highest antibody concentration tested, 335 nM).…”
Section: Preparation Of N9 Mabs a Panel Of 19mentioning
confidence: 99%
“…In the two-dose regimen, the second dose was less reactogenic than the initial dose. 33 Serum sample analysis by Khurana et al . resulted in the identification of novel GP epitopes and, using a pseudo-particle assay in vitro , showed that IgM responses after vaccination are neutralizing, but a second dose administered 28 days after the first one did not significantly increase the antibody titer or repertoire.…”
Section: Introductionmentioning
confidence: 99%